Cross-border marriages in Malaysia: a reflection from survey - Md Said, Muhamad Helmi; Md Hashim, Noraini; Abdul Hak, Nora; Wok, Saodah; Che Soh @ Yusoff, Roslina (AESS Publications, 2020)
The paper aims to discuss the application of the laws and the general understanding of cross-border marriages among Muslims in Malaysia. This socio-legal research used quantitative method and legal doctrinal research. The data have been obtained through the survey with 400 respondents, who have been practising cross-border marriage. The data have been analyzed using Statistical Packages Social Sciences(SPSS) version 22. Research shows that the practice of cross-border marriage among Muslims in Malaysia is caused by the lack of knowledge of those who have been practising cross-border marriages as well as the weaknesses of the implementation of the law. Apart from that, lack of enforcement agencies in Malaysia causes injustice for the parties especially women and children. This vulnerable parties will suffer in terms of social and legal effects. This article is a preamble to a more extensive study of the cross-border marriage which the findings will be useful for further enhancement of the current legal provisions in Malaysia.